Acmeologic bases of scientific and pedagogical personnel training in the conditions of masters program - Turgunbayeva, Botagul Altayevna; Martišauskienė, Elvyda; Bekzhanova, Bakhytzhamal Zhorabekovna; Kelsievna, Valentina Khristofova (Pedagogika, 2014)
Acmeology is considered as a science that studies the achievements of high level professionalism of the individual. The essence of teaching Acmeology is disclosed. Methodological approaches to the study of acmeologic training of Masters are identified. Acmeologic factors that contribute to the professional competence formation of Master’s program students are studied.